(5z-9)(8+z)=0

Simple and best practice solution for (5z-9)(8+z)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5z-9)(8+z)=0 equation:


Simplifying
(5z + -9)(8 + z) = 0

Reorder the terms:
(-9 + 5z)(8 + z) = 0

Multiply (-9 + 5z) * (8 + z)
(-9(8 + z) + 5z * (8 + z)) = 0
((8 * -9 + z * -9) + 5z * (8 + z)) = 0
((-72 + -9z) + 5z * (8 + z)) = 0
(-72 + -9z + (8 * 5z + z * 5z)) = 0
(-72 + -9z + (40z + 5z2)) = 0

Combine like terms: -9z + 40z = 31z
(-72 + 31z + 5z2) = 0

Solving
-72 + 31z + 5z2 = 0

Solving for variable 'z'.

Factor a trinomial.
(-8 + -1z)(9 + -5z) = 0

Subproblem 1

Set the factor '(-8 + -1z)' equal to zero and attempt to solve: Simplifying -8 + -1z = 0 Solving -8 + -1z = 0 Move all terms containing z to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -1z = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -1z = 0 + 8 -1z = 0 + 8 Combine like terms: 0 + 8 = 8 -1z = 8 Divide each side by '-1'. z = -8 Simplifying z = -8

Subproblem 2

Set the factor '(9 + -5z)' equal to zero and attempt to solve: Simplifying 9 + -5z = 0 Solving 9 + -5z = 0 Move all terms containing z to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -5z = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -5z = 0 + -9 -5z = 0 + -9 Combine like terms: 0 + -9 = -9 -5z = -9 Divide each side by '-5'. z = 1.8 Simplifying z = 1.8

Solution

z = {-8, 1.8}

See similar equations:

| x/3=4x/21-7 | | 60x-50=15x-5 | | x/3=4x/21 | | 13-4y+1y= | | 3(m+3)+5(m+1)+-6m=50 | | m=40 | | 6x+3(-3x-7)=0 | | 5x+15=x-20 | | 9xsquared-21=0 | | X-6-x-4=10-c | | -104=5x-3(5x+8) | | .5f=c+6u | | -3+5(b+4)+4(b+3)=2 | | x^(-3/5)=27 | | -7x-6(2x+5)=84 | | 3(n+3)+-2n+2(n+4)=65 | | 8-5x=2c-9x | | 16l=4c^2+9 | | -x/6=5-8 | | 12(t+2)+-7t+-8=6 | | 5x=48+x | | 6sec(x)+8=-4 | | 38.00=0.12m+8 | | -3(-6v+6)-v=2(v-8)-7 | | -5/8x-7.5=7.5 | | -5y=6-4y | | 12(n+1)+-11n+2(n+1)=56 | | 7-3(19z-17)=-4(-2z+18) | | 2g=3g-9 | | -5/8x=0 | | -15+3(b+2)+4(b+1)=2 | | 7h+2=8h-6 |

Equations solver categories